Growth performance and carcass quality of crossbreds pigs from two Pietrain sire lines fed isoproteic diets varying in energy concentration. (April 2016) - Cámara, L.; Berrocoso, J.D.; Coma, J.; López-Bote, C.J.; Mateos, G.G.
Abstract: The effects of net energy (NE) content of isoproteic diets on growth performance and carcass and meat quality traits were studied in crossbreds from Landrace × Large White females and two Pietrain sire lines (PIC L62 vs. German Pietrain). Feed intake (FI) decreased (Lineal, P  < 0.001) and feed efficiency improved (Lineal, P  < 0.001) as the NE content of the diet increased. Crossbreds from PIC L62 had greater ( P  < 0.001) FI and average daily gain (ADG) but were less efficient ( P  < 0.01) than crossbreds from German Pietrain. German Pietrain crossbreds were leaner ( P  < 0.001) and had higher shoulder yield ( P  < 0.01) and less fat at m. Gluteus medius ( P  < 0.001) than carcasses from PIC L62 crossbreds. In summary, an increase in the NE concentration of the diet improved feed efficiency but did not affect ADG. Crossbreeds from PIC L62 sires grew faster and had fatter carcasses than crossbreds from German Pietrain. Highlights: The effects of net energy of the diet on pig growth and carcass merit were studied. No interactions between dietary NE and boar sire line were detected for any trait. An increase in NE improved feed efficiency but did not affect ADG or carcass quality. Energy intake in pigs is likely driven by energy requirement. PIC L62 crossbreds grew faster and had fatter carcass than German Pietrain crossbreds.